Perception and Evaluation of 23 Positive Emotions in Hong Kong and the Netherlands - Sun, Rui; Hou, Wai Kai; Hui, Bryant P. H.; Siu, Nicolson Yat-Fan; Engels, Tiarah; Sauter, Disa A. (Frontiers in Psychology, 2021)
Positive emotions are linked to numerous benefits, but not everyone appreciates the same kinds of positive emotional experiences. We examined how distinct positive emotions are perceived and whether individuals’ perceptions were linked to how societies evaluate those emotions. Participants from Hong Kong and the Netherlands rated 23 positive emotions on their individual perceptions (positivity, arousal, socially engaging) and societal evaluations (appropriate, valued, and approved of). We found that (1) there were cultural differences in judgements of all six aspects of positive emotions; (2) positivity, arousal, and social engagement predicted emotions being positively regarded at the societal level in both cultures; and (3) positivity mattered more for the Dutch, while arousal and social engagement mattered more in Hong Kong for societal evaluations. These findings provided a granular map of perception and evaluation of distinct positive emotions in two cultures, and highlight the role of cultures in the understanding of how positive emotions are perceived and evaluated.